2013
DOI: 10.1111/iju.12352
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless simultaneous bilateral percutaneous nephrolithotomy: Safety, feasibility and efficacy in an Indian setting

Abstract: Abbreviations & AcronymsObjectives: To study the safety, feasibility and efficacy of tubeless simultaneous bilateral percutaneous nephrolithotomy. Methods: We retrospectively studied 85 patients who underwent tubeless simultaneous bilateral percutaneous nephrolithotomy in the Department of Urology, Kasturba Medical College, Manipal, Karnataka, India, from July 2006 to June 2013. The demographic profile and outcomes were compared with the other existing series reported in the literature. Results: A total of 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…However, it must be that the hospital stay is discrepant in different medical centers and that patients experience different simultaneous procedures. 14,20,21 The present results showed that the costs of patients in the simultaneous group were apparently fewer than that in the staged group, and patients could save approximately CNY 7000. It was amazing that the costs of patients were only closely related to total operation time and total postoperative hospital stay according to the univariate and multivariate analyses, rather than different procedures.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…However, it must be that the hospital stay is discrepant in different medical centers and that patients experience different simultaneous procedures. 14,20,21 The present results showed that the costs of patients in the simultaneous group were apparently fewer than that in the staged group, and patients could save approximately CNY 7000. It was amazing that the costs of patients were only closely related to total operation time and total postoperative hospital stay according to the univariate and multivariate analyses, rather than different procedures.…”
Section: Discussionmentioning
confidence: 46%
“…In contrast, patients had to stay longer in the hospital because of fever. However, it must be that the hospital stay is discrepant in different medical centers and that patients experience different simultaneous procedures …”
Section: Discussionmentioning
confidence: 99%
“…1,2 The authors' study presents a retrospective analysis of tubeless simultaneous bilateral percutaneous nephrolithotomy (SBPCNL) in their institution to determine safety, feasibility and efficacy. 3 Although several reports have been published previously, we should state that the present study consisted of a large number of patients, which could provide a significant contribution to this issue. 4,5 The present study also confirms the safety and feasibility of tubeless management of PNL, even in bilateral cases.…”
Section: Editorial Comment Editorial Comment From Dr Karatag Et Al Tmentioning
confidence: 91%
“…On initial assessment at the time of surgery, it was assumed that complete stone clearance was achieved, and hence no nephrostomy was left in situ . The detailed information about supracostal interventions is that “ A total of 14 punctures were supracostal, with five in the 10th to 11th ICS and nine in 11th–12th ICS .” The mentioned line has been taken from the manuscript in the Results section, line 12–14 . No more details were available to compare between the two subgroups, as they were a small subset of patients of whom three required intercostal drainage postoperatively.…”
mentioning
confidence: 99%